2014
DOI: 10.1186/1687-1499-2014-139
|View full text |Cite
|
Sign up to set email alerts
|

A multipath energy-conserving routing protocol for wireless ad hoc networks lifetime improvement

Abstract: International audienceAd hoc networks are wireless mobile networks that can operate without infrastructure and without centralized networkmanagement. Traditional techniques of routing are not well adapted. Indeed, their lack of reactivity with respect to thevariability of network changes makes them difficult to use. Moreover, conserving energy is a critical concern in the design ofrouting protocols for ad hoc networks, because most mobile nodes operate with limited battery capacity, and the energydepletion of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 32 publications
0
39
0
Order By: Relevance
“…The on-demand energy-based forwarding strategy (OEFS) enables the nodes to consume less energy but the route selection criterion is not based on reliability [2]. In [19], a protocol based on energy efficient routing was proposed, named AOMR-LM, which is an improvement on AOMDV [20]. Our approach discovers the route in such a way that it can reduce data redundancy and minimize the traffic overhead, which aids in the power conservation and leads to the enhancement of network life time.…”
Section: Review Of the State Of The Art And Main Contributions Of Thementioning
confidence: 99%
See 1 more Smart Citation
“…The on-demand energy-based forwarding strategy (OEFS) enables the nodes to consume less energy but the route selection criterion is not based on reliability [2]. In [19], a protocol based on energy efficient routing was proposed, named AOMR-LM, which is an improvement on AOMDV [20]. Our approach discovers the route in such a way that it can reduce data redundancy and minimize the traffic overhead, which aids in the power conservation and leads to the enhancement of network life time.…”
Section: Review Of the State Of The Art And Main Contributions Of Thementioning
confidence: 99%
“…The lemma states that the routing overhead increases (in either cases proactive or reactive protocols) with mobility, which can be expressed using Equations (19) and (20).…”
Section: Lemma-1mentioning
confidence: 99%
“…By the simulation results it showed that this key management guarantees key substantiation, enhances fault-tolerance and defends the tree from impersonation attacks. Mekkakia et al (2014) [8] anticipated a single-path routing technique; a novel path-discovery course is required once a path break down is detected, and this procedure causes delay and exhaustion of node resources. A multipath routing technique is an unconventional to exploit the network lifetime.…”
Section: ) Processor Power Managementmentioning
confidence: 99%
“…Network lifetime [25][26][27][28][29] is one of the most prominent barriers in deploying ad hoc networks for large-scale applications. Our new algorithm helps to enhance the lifetime of the network by taking care of nodes energy.…”
Section: A Adapting Pheromone Quantity To the Link Cost And The Energymentioning
confidence: 99%